Mali : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
Gold mining represents an engine of growth for the Malian economy. A description of the techniques and importance of artisanal gold mining in Mali, the key developments of the industrial mining era, and potential gold mining developments are discussed in the paper. The Malian mining policy and regulations, the impact of industrial gold mining on the Malian economy, public finances, and employment are discussed. The statistical data on the economic indices of Mali are also presented in the paper.